Democratic Republic of Timor-Leste : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
The Joint Staff Advisory Note focuses on the Poverty Reduction Strategy Paper (PRSP) for the Democratic Republic of Timor-Leste. It highlights that the authorities are presenting Timor-Leste's National Development Plan 2002 (NDP) and associated implementation documents to the Boards to indicate the progress achieved by the country during the past three years. The note outlines key elements in NDP design and implementation, and identifies key challenges faced in NDP implementation. It also provides suggestions for both strengthening the strategy and addressing implementation risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet